Practice in a Pandemic: School Social Workers' Adaptations and Experiences During the 2020 COVID-19 School Disruptions. Issue 3 (July 2021) - Kelly, Michael S.; Benbenishty, Rami; Capp, Gordon; Watson, Kate; Astor, Ron
In March 2020, as American PreK-12 schools shut down and moved into online learning in response to the global COVID-19 pandemic, there was little information about how school social workers (SSWs) were responding to the crisis. This study used a national online survey to understand how SSWs ( N = 1, 275) adapted their school practice during the initial 2020 COVID-19 crisis. Findings from this study indicate that SSWs made swift and (relatively) smooth adaptations of their traditional practice role to the new context, though not without reporting considerable professional stress and personal challenges doing so. SSWs reported significant concerns about their ability to deliver effective virtual school social work services given their students' low motivation and lack of engagement with online learning, as well as significant worries about how their students were faring during the first months of the pandemic. Implications for school social work practice, policy, and research are discussed.